IMPORTANCE OF SECOND LEVEL BANKS AT THE STAGE OF MODERNIZATION OF THE ECONOMY OF KAZAKHSTAN - Zhadigerova O.Zh.; Kadyrova G.M (Academic Journal of Physical and Chemical Sciences, 2019)
The article discusses the role of development of second banks (STB) in the context of the implementation of the third modernization of the economy of Kazakhstan. According to the authors, a developed banking system is the basis of a modernized economy, and therefore, there is a growing need for the operation of several large universal banks that accumulate large amounts of financial resources. Financial intermediation of second-tier banks will allow business entities wishing to efficiently manage their money capital to become strategic investors in the economic modernization of Kazakhstan. Therefore, it is important to study the problems and prospects for the development of banking in the conditions of growing uncertainty and cyclical development of the economy. An important condition for a full-fledged and high-quality financing of the modernization process is to achieve sustainability of the financial system of Kazakhstan, where second-tier banks play an important role.